The Agricultural Conservation Planning Framework: Opportunities and challenges in the eastern United States. Issue 3 (14th September 2021) - Duncan, Jonathan M.; Respess, Zachary; Ryan, William; Austin, Robert; Royer, Matthew; Osmond, Deanna; Kleinman, Peter
Abstract: The Agriculture Conservation Planning Framework (ACPF) applies high‐spatial resolution soils and topographic data, now available for many areas of the United States, to precisely locate opportunities for the placement of conservation practices in agricultural watersheds. Application of the ACPF, developed in midwestern landscapes, to watersheds in the eastern United States represents both opportunity and challenge to conservation planning. Based on experience in applying ACPF to eight watersheds in the eastern United States, from Vermont to North Carolina, we assess the toolbox's application in the eastern United States through the lens of strengths, weaknesses, opportunities, and threats (SWOT) analysis framework. We see a great future for the ACPF, but its adoption and utility require interaction with scientists and conservation planners familiar with the region to avoid misapplication and ensure appropriate adaptation and interpretation. Abstract : Core Ideas The Agriculture Conservation Planning Framework (ACPF) is a spatial tool not yet well tested in the eastern USA. Parts of the toolbox work quite well in eastern U.S. landscapes. Other parts of the toolbox leave questions for application and interpretation.